Answer

(4h/√2)+4h

Explanation:

the side length as a function of h will be needed, so we will compute it first,

Let x be the side length of the right isosceles triangle, then using Pythagorean theorem.

CHECK THE ATTACHMENT FOR DETAILED EXPLANATION

(3/4)x+(3/2)x=9/4

(3/4)x+(3.2/2.2)x=9/4

(3/4)x+(6/4)x=9/4

3x+6x=9

9x=9

x=1

**Answer:**

non all of the students like there class

**Step-by-step explanation: 20+10+15+05=50**

**Answer:**

8ab

**Step-by-step explanation:**

<h3>

**Answer: g(f(x)) = 4x^2 - 4x - 3**</h3>

Work Shown:

g(x) = x^2 - 4

g(f(x)) = ( f(x) )^2 - 4

g(f(x)) = ( 2x-1 )^2 - 4

g(f(x)) = (2x-1)(2x-1) - 4

g(f(x)) = 4x^2-2x-2x+1 - 4

**g(f(x)) = 4x^2 - 4x - 3**